2004
DOI: 10.1007/s11218-004-5764-2
|View full text |Cite
|
Sign up to set email alerts
|

Parents? satisfaction with their child?s first year of school

Abstract: A group of university and vocationally educated parents (n = 486) were requested to evaluate their satisfaction with their child's first school year, and they were also asked to recall the positive and negative events from their child's academic year. Both structured and open-ended measures consistently revealed that parents were quite satisfied with the functioning of their child's school. Parents' social-psychological distance from the school, as measured by their social positions in the education hierarchy,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 16 publications
3
11
1
Order By: Relevance
“…Parallel observations on the relationship of the parent's educational position and gender to satisfaction were made in our study of parents' perceptions of their child's first school year, suggesting that vocationally educated fathers are the group that is the most distant from the school (Räty et al 2004). Additional evidence was obtained in a recent survey of Finnish parents' participation in their children's schooling, indicating that academically educated mothers and vocationally educated fathers form opposite groups in regard to participation in parents' evenings, cooperation committees and related occasions ).…”
supporting
confidence: 59%
See 1 more Smart Citation
“…Parallel observations on the relationship of the parent's educational position and gender to satisfaction were made in our study of parents' perceptions of their child's first school year, suggesting that vocationally educated fathers are the group that is the most distant from the school (Räty et al 2004). Additional evidence was obtained in a recent survey of Finnish parents' participation in their children's schooling, indicating that academically educated mothers and vocationally educated fathers form opposite groups in regard to participation in parents' evenings, cooperation committees and related occasions ).…”
supporting
confidence: 59%
“…Our qualitative findings derived from the child's first and third school years indicated that mothers gave more positive reports of the teachers than the fathers did (Räty et al 2004;2005). Moreover, the mothers were concerned about the problems in their child's schooling, reporting more negative events, especially ones pertaining to home-school cooperation, than the fathers did.…”
mentioning
confidence: 75%
“…At any rate, the academically educated mothers are the group that tends to be the most active, and also the most demanding and critical (see also Lareau, 1987;Realy, 1998), in their relationship to the school, as was also shown by our own earlier study. In the present study, the parents of boys and girls did not differ from each other in regard to satisfaction, which accords with our earlier observations (Räty, Jaukka, & Kasanen, 2004).…”
Section: Discussionsupporting
confidence: 93%
“…The vocationally educated fathers stood out as a group again, then, as they did in our earlier study of first-graders' parents (Räty, Jaukka, & Kasanen, 2004), in which this group was found to indicate less satisfaction than the other groups with the functioning of their child's school. We interpreted this finding to mean that working-class fathers, as a social group, are the furthest from the middle-class school culture.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation